The ancient Mediterranean trade in ceramic building materials : a case study in Carthage and Beirut - Mills, Philip (Roman and late antique Mediterranean pottery, 2013)
This study addresses the level of interregional trade of ceramic building material (CBM), traditionally seen as a high bulk low value commodity, within the ancient Mediterranean between the third century BC and the seventh century AD. It examines the impact of different modes of production, distribution and consumption of CBM and how archaeological assemblages differ from what is predicted by current models of the ancient economy. It also explores how CBM can be used to investigate cultural identity and urban form.